Ritual Adat Nawu Nu Maje di Masyarakat Desa Petuntawa dan Riangbao Dalam Perspektif Hukum Islam - Iskandar, Iskandar; Langoday, Nurahmi Nahdyah (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
At the beginning of the planting season, the people of Riangbao and Petuntawa villages will perform the Nawu Nu Maje ritual with the aim that all kinds of plants and harvests will not be eaten by pests so that it is carried out every year at the beginning of the planting season because it can affect the harvest. This study aims to examine and analyze the Nawu Nu Maje traditional ritual carried out by the people of Petuntawa and Riangbao villages in an effort to expel pests, and to view it from the perspective of Islamic law. This study uses a qualitative approach using in-depth interviews as the main instrument for data collection. Key informants involved in this study include traditional leaders, religious leaders, and communities who actively participate in the Nawu Nu Maje ritual. Descriptive data analysis aims to reveal the meaning, symbolism, and impact of the ritual on the religious life of the community. The results of the study show that the Nawu Nu Maje traditional ritual is still widely practiced by the people of Petuntawa and Riangbao villages as a traditional way to repel pests that attack plants. However, from the perspective of Islamic law, this ritual is included in the category of shirk because it is a form of asking for help from creatures or powers other than Allah. Shirk is a major sin in Islam that is strictly prohibited and damages the principle of monotheism. This study concludes that society needs to gain a deeper understanding of the dangers of shirk and the importance of purifying worship only to Allah. It is recommended that more intensive religious education, training and counseling be held, as well as dialogue between traditional and religious leaders to find solutions that are in accordance with Islamic teachings without eliminating positive cultural values.